HPLC Method for Simultaneous Analysis of Ranitidine and Metronidazole in Dosage Forms - David King'ori, Loti; B. Walker*, Roderick (Asian Journal of Chemistry, 2014)
A simple, rapid, precise and accurate stability indicating HPLC method for the simultaneous analysis of metronidazole and ranitidine in dosage forms has been developed and validated. Calibration curves for metronidazole and ranitidine exhibited linearity (R2 = 0.9995 for both compounds) over the concentration ranges investigated. The method was sensitive, selective and accurate for both compounds. Both drugs were found to be stable following acid hydrolysis studies. However, following alkali hydrolysis degradation of both compounds was observed. Furthermore metronidazole appeared to be stable following oxidative studies however ranitidine underwent complete degradation under these conditions. Both drugs were well resolved from the degradation products. The stability indicating chromatographic method has the necessary precision and accuracy for the simultaneous analysis of metronidazole and ranitidine in dosage forms.